Transecting securityscapes : dispatches from Cambodia, Iraq, and Mozambique - Paasche, Till F.; Sidaway, James D. (Athens : The University of Georgia Press, 2021)
"Transecting Securityscapes draws on over a decade of fieldwork and participant observation by the co-authors from three conflicted contexts - Cambodia, the Kurdistan region of Iraq and Mozambique. The book pushes critical geopolitics, still often theory-led and discourse-bound, into terrains of the everyday, developing on a method of urban and territorial transects, combined with a range of other methods and modes of encounter. The three research sites enable comparative reflections on diversity and commonality in "securityscapes", studying both long-term networks and short-term circuits. Intersections between "security", power and political economy are examined in the contexts of empire, decolonization, revolution, Cold War and its aftermaths. The result is a book of wide interest; for scholarship on each of the research sites, for others developing qualitative methods in security studies, urban and political geography and for all analysts of conflict, violence and peace"--
Situating securityscapes -- Transecting securityscapes -- Maputo's fractures -- The fall and rise of Phnom Penh -- Kurdistan: the fire next time -- The world does not exist for our theories.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Security sector -- Mozambique; Internal security -- Mozambique; Security sector -- Iraq; Internal security -- Iraq; Security sector -- Cambodia; Internal security -- Cambodia; Internal security; Security sector; Cambodia; Iraq; Mozambique; Electronic books